Empowering Rural Economies: The Impact of MSME Development on Welfare in Binjeita Village, Indonesia - Selvina Baba; Syarwani Canon; Sudirman Sudirman; Frahmawati Bumulo; Ardiansyah (Jurnal Pendidikan Ekonomi dan Bisnis, 2025)
This study investigates the influence of Micro, Small, and Medium Enterprise (MSME) development on community welfare in Binjeita Village, North Sulawesi, Indonesia, a rural area with 132 active MSMEs. The research addresses the gap between government support for MSMEs and actual welfare outcomes, aiming to empirically assess whether MSME performance translates into tangible improvements in income, education, and health. Using a quantitative, positivist approach and a simple causal design, data were collected from 33 randomly selected MSME actors. Instruments measuring MSME development and community welfare were validated and found to be highly reliable (Cronbach’s alpha > 0.90). Descriptive and inferential statistics, including simple linear regression, were employed to test the hypothesis. Results indicate that MSME development is rated as "very good," particularly in the financial aspect, while community welfare also scored "very good," with education emerging as the strongest component. The regression analysis yielded a positive and statistically significant coefficient (b = 0.821; t = 6.588; p < 0.001), confirming that improved MSME performance correlates with increased welfare. The model explains 58.3% of welfare variation, highlighting the substantial role of MSMEs in local development. These findings suggest that policies aiming to empower MSMEs—through finance, training, and market access—can effectively improve rural welfare. The study contributes to local development literature by offering empirical evidence of the MSME-welfare nexus in an under-researched Indonesian village context.